2018
DOI: 10.3390/su10093266
|View full text |Cite
|
Sign up to set email alerts
|

Do Large Slaughterhouses Promote Sustainable Intensification of Cattle Ranching in Amazonia and the Cerrado?

Abstract: This study investigated the influence of large slaughterhouses on five variables, two related to environment impact (land use change rate and greenhouse gases emissions (GE)), and three related to cattle-ranching intensification (protein from crops, calories from crops and stocking rate). In Amazonia, the results show a reduction of the land use change rate and GE in zones both with and without the influence of large slaughterhouses. The hypothesis that slaughterhouses are leverage points to reduce deforestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Brazilian livestock production is also considered in the paper by Santos and Costa [11]. They tested the hypothesis according to which large slaughterhouses are potential leverage points for promoting sustainable intensification in the beef supply chain in Amazonia and the Cerrado, due to their interactions with ranchers, their location at the agricultural frontier, and their ability to control access to the market.…”
mentioning
confidence: 99%
“…Brazilian livestock production is also considered in the paper by Santos and Costa [11]. They tested the hypothesis according to which large slaughterhouses are potential leverage points for promoting sustainable intensification in the beef supply chain in Amazonia and the Cerrado, due to their interactions with ranchers, their location at the agricultural frontier, and their ability to control access to the market.…”
mentioning
confidence: 99%
“…While supply zones have been used to analyze slaughterhouse influence, accurately delineating these zones has proven difficult due to data constraints. While other studies have suggested different methods to delineate the zones, including creating buffers around slaughterhouse coordinates [14], estimating maximum purchasing distances [10], and using trip lengths [28], they are mostly best guesses for direct suppliers and do not consider the full supply chain. This has resulted in imprecise zone boundaries, which impedes a comprehensive understanding of the dynamics within slaughterhouse supply chains.…”
Section: Introductionmentioning
confidence: 99%